Investigating gender effects on interpreter style: A corpus-based multidimensional study of Chinese-English institutional interpreting - Yuan, Xiaoshu; Shi, Yunzhang (Transletters. International Journal of Translation and Interpreting, 2025)
This research investigates gender-related style differences in diplomatic interpreting using multidimensional corpus analysis. It was found that while female and male interpreters demonstrate convergent styles marked by informational focus and persuasive explicitness, significant divergences emerge in 14 linguistic parameters. Analysis reveals that shared fidelity to source texts creates stylistic uniformity, whereas varying social expectations and pragmatic factors influence gender-specific linguistic choices. The findings challenge assumptions about gendered interpreting styles, highlighting how professional norms mediate biological differences in diplomatic discourse contexts.